Turismo y representación del paisaje. La invención del sur de Chile en la mirada de la Guía del Veraneante (1932-1962) - Rodrigo Booth (Centre de Recherches sur les Mondes Américains, 2008)
This work studies the shape of the modern territorial imaginary in relation with tourism in Chile during the second third of 20th century. To know the character of the tourist national landscape, the article studies the iconographic representations presented in the Guia del Veraneante, main tourist guide in Chile, edited by the Company of the Railroads of the State between 1932 and 1962. It is proposed that the tourism state organization and his device of propaganda propitiated the conversion of extensive empty territories in tourist attractive sceneries for the majority of Chileans. It insertion would have determined the shape of a modern image for Chile. To verify this hypothesis, there will be analyzed the case of the landscape commonly known as "South".